2012
DOI: 10.2527/jas.2011-4285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequential feeding of β-adrenergic agonists on cull cow performance, carcass characteristics, and mRNA relative abundance

Abstract: The objectives of this study were to determine the effects of supplementation with a single β-adrenergic agonist (β-AA) or a sequence of β-AA on cow performance, carcass characteristics, and mRNA relative abundance of cull cows implanted and fed a concentrate diet. Sixty cull cows were implanted with Revalor-200 (200 mg of trenbolone acetate and 20 mg of estradiol) and assigned to 1 of 4 treatments (n = 15/treatment): CON = fed a concentrate diet only; RH = supplemented with ractopamine-HCl for the last 25 d b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244]. …”
Section: Discussionsupporting
confidence: 79%
“…Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244]. …”
Section: Discussionsupporting
confidence: 79%
“…Kellermeier et al (2009) reported that total collagen decreased in ZH supplemented cattle and muscle fiber diameter increased in conjunction, likely yielding a dilution effect in collagen concentration. In our study, LM area did not increase significantly (93.6 cm 2 for ZH versus 83.6 cm 2 for C, P = 0.18; Weber et al, 2012), so muscle hypertrophy in ZH-supplemented cows likely was not sufficient to yield a difference in total collagen content; however, collagen solubility in ZH-treated cows (ZH and RH + ZH treatments) increased compared with C cows and increased (P b 0.05) in the RH + ZH treatment compared with RH cows. We postulate that this increase is due to a higher percentage of newly synthesized collagen.…”
Section: Non-enhanced Longissimus Warner Bratzler Shear Force and Sencontrasting
confidence: 63%
“…Steaks used for WBSF measurements were not frozen, but sensory steaks were frozen at − 40°C until sensory panels could be conducted. The 9-10-11th rib section was used for carcass composition prediction (Weber et al, 2012).…”
Section: Enhancementmentioning
confidence: 99%
“…To date, much of the research conducted on mature cow meat quality has focused on improving carcass traits, lean colour, and palatability of mature cows through increasing the nutritional plane before slaughter (Brown and Johnson 1991;Boleman et al 1996;Cranwell et al 1996;Schnell et al 1997;Rider-Sell et al 2004;Stelzleni et al 2007;Weber et al 2012). However, research has been conducted to profile quality attributes among the United States maturity grades C/D and E (Jones et al 2004).…”
Section: Introductionmentioning
confidence: 99%